Molecular characterisation of a germplasm bank for theobroma genus using the rapd technique (2004)
RAPD markers (Random Amplified Polymorphic DNA) were used for analysing 145 individuals (128 T. grandiflorum and 17 T. bicolor) from the ex situ Theobroma genus germplasm bank at Instituto Sinchi, located at San José del Guaviare. 5 primers able to generated polymorphism were selected from an initial set of 20, generating 114 bands that enable to us to distinguish between more than 99% of individuals analysed: 57 bands for T. grandiflorum (84.2% polymorphic), 45 bands for T. bicolor (26.7% polymorphic) and 12 bands shared between the two species (58.3% polymorphic). A high degree of intra-specific similarity particularly in T. bicolor was established from the similarity matrix obtained by using the Dice index and represented in a UPGMA dendrogram and the principal components analysis (PCA). The comparison of this analysis with a previous morpho-agronomic evaluation of some T. grandiflorum individuals revealed that the groups generated on the basis of its agronomic and morphological traits were heterogeneous at molecular level. The obtained information will be used as a tool in strategies regarding maintenance, enrichment and use of the germplasm bank. Key words: Theobroma grandiflorum, Theobroma bicolour, RAPD, molecular characterisation.